Riociguat for the treatment of pulmonary hypertension: a safety evaluation. Issue 12 (1st December 2016) - Binder, Christina; Zotter-Tufaro, Caroline; Bonderman, Diana
ABSTRACT: Introduction: The development of pulmonary hypertension (PH) has multifactorial underlying pathophysiological causes and can be classified into five groups. While three different classes of therapeutic drugs are licensed for the treatment of pulmonary arterial hypertension (PAH, WHO group 1), specific medical therapies are lacking for other forms of PH, such as PH due to left heart disease. In 2013 riociguat, a first-in class soluble guanylate cyclase stimulator, has also become available for the treatment of PAH. Riociguat was further introduced as the first approved pharmacotherapy for the treatment of patients with chronic thromboembolic PH (WHO group 4, CTEPH). Despite these advances in therapeutic options for patients with PH, none of these agents have been approved for the treatment of PH due to left heart disease. Areas covered: We aim to give an overview of the pathophysiology of PH, pharmacodynamics and pharmacokinetic properties, safety and efficacy of riociguat, including adverse events, contraindications and drug interactions. Expert opinion: Considering the increasingly broad indications for riociguat in patients with PH, substantial knowledge of data and properties on safety and efficacy of riociguat are becoming more and more important for physicians prescribing riociguat to PH patients.